What makes a good bat box? How box occupancy depends on box characteristics and landscape‐level variables - Sandra Pschonny; Jan Leidinger; Rudolf Leitl; Wolfgang W. Weisser (Ecological Solutions and Evidence, 2022)
Abstract Bat populations are in steep decline and presently, 16% of all species are classified as ‘threatened’. One main driver identified for this decline is the loss of natural roosting opportunities, caused by the removal of natural habitats. Installation of bat boxes is one solution to compensate for the lack of natural roosting opportunities. Current recommendations for box design emphasize low maintenance costs and are rarely based on empirical evidence. We investigated occupancy of 13,634 bat boxes in northern Bavaria, Germany. In our study, boxes differed in type, age and mounting height, as well as in maximum community age, that is the length of time a group of boxes had been installed in a particular place, the size of box groups and the distance to the next box in the surrounding area, that is box isolation. Our results showed that box occupancy depended on box type and bat species. As a case study, we analysed the two most common species found within the investigated boxes, Pipistrellus pipistrellus and Myotis nattereri, in more detail. Both species showed preference to a voluminous box that had a narrow entrance (‘Gable box’ 14 mm). For P. pipistrellus, only box type affected occupancy, whereas for M. nattereri, the relationship between box type and box age was important. Older boxes and boxes in areas with higher maximum community age of boxes showed higher box occupancy by bats. Box occupancy decreased with the distance between adjacent box groups (‘box isolation’). High mounting height showed a tendency for increased box occupancy, but the effect was only weakly significant. Because of the species‐specific responses in our study, we suggest installing a combination of different box types, including at least one box type with a narrow entrance (14 mm). Boxes should be placed as box groups of three to four boxes, and there should be short distances between adjacent box groups. We also recommend installing new box groups close to areas of high maximum community age of boxes.